COMMUNICATION PROBLEMS AT THE UNIVERSITY OF GOMA "UNIGOM" - Butotima, Aimé; N'SII, Gloire MAOMBI; Mungazi, Cosmas; Mulonda, Mustapha; Kasongo, Rashidi (IJRDO- Journal of Educational Research, 2023)
This practical work of the English seminary, presented in the setting of the Doctoral school of the university National Educational UPN-UNIGOM given by the Professor Ordinaire Mbukani carries on" the problems or obstacles of the communication in an academic institution ", case of the University of Goma. The choice of this academic institution is not a fact of the luck", like all communication was never at random ". Because the UNIGOM is the biggest official university that the city of Goma counts, curiously that knows several problems that affect his/her/its wanted picture by his/her/its publics.